Decoding Pragmatic Strategies in Ferdy Sambo's Plea: Seeking a Glimpse of Hope in the Claustrophobic Courtroom - Elfrida, Rotua; Sihite, Jubilezer; Ketaren, Selfiyani (CV. Creative Tugu Pena, 2024)
The prevailing research inadequately explores the pragmatic strategies within courtroom discourse, particularly in non-Western legal systems such as Indonesia. This study embarks on bridging this gap by analyzing pragmatic strategies employed in Ferdy Sambo's plea within the Indonesian legal environment. Utilizing qualitative methods encompassing discourse and pragmatic analysis, this study scrutinizes the deployment of linguistic techniques and pragmatic strategies to meet communicative objectives. The investigation unveils a meticulous utilization of assertive and declarative illocutionary acts, demonstrating a narrative woven with assertiveness, seeking validation and empathy in the claustrophobic courtroom atmosphere. Furthermore, it revealed the significance of understanding the intricate relationship between societal norms, values, and the narrative crafted within a plea, especially in culturally rich contexts like Indonesia. This endeavor enhances the comprehension of the pragmatic strategies in Ferdy Sambo's plea and delineates the broader societal influences that dictate the narrative dynamics within the Indonesian legal discourse. Through this lens, the study contributes substantially to pragmatics, discourse analysis, and legal communication, inviting further nuanced research. Keywords: Pragmatics, Ferdy Sambo, Claustrophobic Courtroom, Glimpse